Historical analysis of leptospirosis cases in the municipality of Belém-PA, from 2013 to 2017 (Research, Society and Development, 2020)
Objectives: The present study aimed to analyze the historical series of leptospirosis cases in the city of Belém-PA and to identify the neighborhoods with the highest number of notified cases of the disease, aiming to contribute to possible preventive measures. Methodology: It is a quantitative, retrospective, descriptive-exploratory study based on epidemiological data yielded by Municipal Health Department (SESMA), from 2013 to 2017. Results: 758 cases of leptospirosis have been identified, with a greater prevalence in the neighborhoods of Guamá, Pedreira, Marambaia, Marco and Tapanã. There was a reduction in the percentage of cases during the study period. In addition, in relation to the housing area and infection site, highlighted urban center with 91.5% (692/758) of notifications, followed by 18.6% (141/758) of cases related to the home environment. Conclusion: This research demonstrated that leptospirosis is still present in the city of Belém-PA, mainly in some neighborhoods such as Guamá, which had the highest number of notifications. This finding reinforces the importance of creating public policies aimed at the local socio-environmental reality, in order to contribute to the prevention of the problem in the population.